Sediment source fingerprinting as an aid to large-scale landscape conservation and restoration: A review for the Mississippi River Basin. (15th December 2022) - Xu, Zhen; Belmont, Patrick; Brahney, Janice; Gellis, Allen C.
Abstract: Reliable quantitative information on sediment sources to rivers is critical to mitigate contamination and target conservation and restoration actions. However, for large-scale river basins, determination of the relative importance of sediment sources is complicated by spatiotemporal variability in erosional processes and sediment sources, heterogeneity in sediment transport and deposition, and a paucity of sediment monitoring data. Sediment source fingerprinting is an increasingly adopted field-based technique that identifies the nature and relative source contribution of sediment transported in waterways. Notably, sediment source fingerprinting provides information that is independent of other field, modeling, or remotely sensed techniques. However, the diversity in sampling, analytical, and interpretive methods for sediment fingerprinting has been recognized as a problem in terms of developing standardized procedures for its application at the scale of large river basins. Accordingly, this review focuses on sediment source fingerprinting studies conducted within the Mississippi River Basin (MRB), summarizes unique information provided by sediment source fingerprinting that is distinct from traditional monitoring techniques, evaluates consistency and reliability of methodological approaches among MRB studies, and provides prospects for the use of sediment source fingerprinting as an aid to large-scale landscape conservation and restoration under current management frameworks. Most MRB studies reported credible fingerprinting results and found near-channel sources to be the dominant sediment sources in most cases, and yet a lack of standardization in procedural steps makes results difficult to compare. Findings from MRB studies demonstrated that sediment source fingerprinting is a highly valuable and reliable sediment source assessment approach to assist land and water resource management under current management frameworks, but efforts are needed to make this technique applicable in large-scale landscape conservation and restoration efforts. We summarize research needs and discuss sediment fingerprinting use for basin-scale management efforts with the aim of encouraging that this technique is robust and reliable as it moves forward. Highlights: Sediment fingerprinting studies within the Mississippi River Basin were reviewed. Most studies considered near-channel sources as the dominant sediment sources. Comparability of studies suffers from a lack of standardization in procedural steps. Sediment fingerprinting is a reliable technique under current management frameworks. Efforts are needed to make this approach applicable to large-scale landscapes.